(untitled) (The Conference Hub, 2025)
This article discusses the theoretical and methodological foundations of designing a system of mobile educational methods and the mechanisms for its effective implementation in the educational process. Methodological approaches based on mobile devices, digital applications and interactive learning platforms are analyzed, indicating the didactic advantages of the mobile educational system, the possibilities of individualizing the educational process and its role in supporting the independent learning activities of students. Also, the stages of pedagogical design in the implementation of mobile education, technological requirements, application strategies in educational institutions and criteria for effectiveness are analyzed. The results of the study show that careful design of the system of mobile educational methods can improve the quality of education, form the student as an active subject and expand the possibilities of continuous learning.